Desain dan Fabrikasi Alat Ukur Temperatur dan Kelembaban Udara Dalam Tanah Berbasis Mikrokontroler ATMega8535 - Hidayat, Arif; Sugriwan, Iwan; Harnawan, Ade Agung (Jurnal Fisika FLUX, 2017)
Measuring device that used for measuring temperature and humidity inside soil digitally has been realized. The measuring device tested on soil along building foundation with putting SHT11 sensor inside soil using biopory drilling machine. The length of drill is 120 cm with 3, 5 diameter. The sensor is placed 5 cm from the end of the bottom drilling pipe clamped with rubber and styrofoam. In the drilling pipe there is an air hole that function is for air from the soil got into the sensor. The measurement done in 1 day, in each deep 20, 40, 60, 80, 100, and 120 cm. The maximum air temperature inside soil is 27,60C in the depths 120 cm and the minimum is 23,30C in the depths 60 cm. The maximum air humidity inside soil is 96,8 % in the depths of 60 cm and the minimum is 31,4 % in the depths of 100 cm. The data result of measurement is shown on the 16x2 LCD and laptop, using interface software and automatically save the data into Excel and database.